The inversion of the Control Region in three mitogenomes provides further evidence for an asymmetric model of vertebrate mtDNA replication. - Miguel M Fonseca (Public Library of Science (PLoS), 2014)
Mitochondrial genomes are known to have a strong strand-specific compositional bias that is more pronounced at fourfold redundant sites of mtDNA protein-coding genes. This observation suggests that strand asymmetries, to a large extent, are caused by mutational asymmetric mechanisms. In vertebrate mitogenomes, replication and not transcription seems to play a major role in shaping compositional bias. Hence, one can better understand how mtDNA is replicated--a debated issue--through a detailed picture of mitochondrial genome evolution. Here, we analyzed the compositional bias (AT and GC skews) in protein-coding genes of almost 2,500 complete vertebrate mitogenomes. We were able to identify three fish mitogenomes with inverted AT/GC skew coupled with an inversion of the Control Region. These findings suggest that the vertebrate mitochondrial replication mechanism is asymmetric and may invert its polarity, with the leading-strand becoming the lagging-strand and vice-versa, without compromising mtDNA maintenance and expression. The inversion of the strand-specific compositional bias through the inversion of the Control Region is in agreement with the strand-displacement model but it is also compatible with the RITOLS model of mtDNA replication.